WHO Environmental Noise Guidelines for the European Region: A Systematic Review on Environmental Noise and Adverse Birth Outcomes - Nieuwenhuijsen, Mark J; Ristovska, Gordana; Dadvand, Payam (MDPI AG, 2017)
Introduction: Three recent systematic reviews suggested a relationship between noise exposure and adverse birth outcomes. The aim of this review was to evaluate the evidence for the World Health Organization (WHO) noise guidelines and conduct an updated systematic review of environmental noise, specifically aircraft and road traffic noise and birth outcomes, such as preterm birth, low birth weight, being small for gestational age and congenital malformations. Materials and methods: We reviewed again all the papers on environmental noise and birth outcomes included in the previous three systematic reviews and conducted a systematic search on noise and birth outcomes to update previous reviews. Web of Science, PubMed and Embase electronic databases were searched for papers published between June 2014 (end date of previous systematic review) and December 2016 using a list of specific search terms. Studies were also screened in the reference list of relevant reviews/articles. Further inclusion and exclusion criteria for the studies provided by the WHO expert group were applied. Risk of bias was assessed according to criteria from the Newcastle-Ottawa quality assessment scale for case-control and cohort studies. Finally, we applied the GRADE principles to our systematic review in a reproducible and appropriate way for judgment about quality of evidence. Results: In total, 14 studies are included in this review, six studies on aircraft noise and birth outcomes, five studies (two with more or less the same population) on road traffic noise and birth outcomes and three related studies on total ambient noise that is likely to be mostly traffic noise that met the criteria. The number of studies on environmental noise and birth outcomes is small and the quality of evidence generally ranges from very low to low, particularly in case of the older studies. The quality is better for the more recent traffic noise and birth outcomes studies. As there were too few studies, we did not conduct meta-analyses. Discussion: This systematic review is supported by previous systematic reviews and meta-analyses that suggested that there may be some suggestive evidence for an association between environmental noise exposure and birth outcomes, although they pointed more generally to a stronger role of occupational noise exposure, which tends to be higher and last longer. Very strict criteria for inclusion and exclusion of studies, performance of quality assessment for risk of bias, and finally applying GRADE principles for judgment of quality of evidence are the strengths of this review.
Keywords: congenital abnormality; congenital anomaly; gestation; noise; pregnancy; prematurity; quality of evidence